Management of advanced penile cancer - Wullenkord, Ramona; Giannatempo, Patrizia; Nicolai, Nicola; Garcia del Muro, Xavier (Oncology research and treatment, 2025)
Background: Penile cancer is a rare, aggressive malignancy, with incidence varying geographically. The primary risk factor is human papillomavirus (HPV) infection. Squamous cell carcinoma represents the most common histological subtype, accounting for around 95% of cases. For advanced penile carcinoma, prognosis remains poor with a 5-year survival rate of 16% in stage IV disease. Treatment is largely centred on palliative systemic therapy. This review provides an overview of the evidence on palliative systemic treatment for advanced penile cancer, including chemotherapy, immunotherapy, and targeted therapy, as well as emerging treatment strategies. Summary: Cisplatin-based chemotherapy is the established first-line treatment for advanced penile cancer, but its efficacy is often limited and short-lived. Immune checkpoint inhibitors showed limited but promising efficacy in penile carcinoma, with some patients experiencing durable responses, particularly those with high tumour mutational burden, HPV positivity, or high PD-L1 expression, though further research is needed to identify predictive biomarkers for optimal patient selection. HPV vaccine-based therapies targeting HPV oncoproteins, adoptive T-cell therapies and agents like binatrafusp alfa are showing potential in HPV-associated cancers, though their role in penile cancer remains uncertain. Ongoing clinical trials are investigating potentially synergistic combination therapies, such as HPV vaccines with checkpoint inhibitors or immune therapies combined with chemotherapy or tyrosine kinase inhibitors. Key Messages: Cisplatin-based chemotherapy remains the first-line treatment for advanced penile cancer, while immunotherapy and targeted therapies show promise but require further investigation. Enrolling patients in clinical trials and conducting early tumour molecular sequencing, if possible, are crucial for improving outcomes and identifying effective treatment targets.